Contemporary Hazards for Drivers - Bałuszyński, Sławomir; Kluczewska-Chmielarz, Kamila; Lis, Dawid (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
A person driving a vehicle should be aware that they are responsible not only for their own safety and the safety of passengers during the trip but also for the safety of other road users – they must not pose a danger to them. One of the essential elements that can impact safety in land traffic is medical examinations. However, not all drivers are subject to periodic medical checks after obtaining their driving license. The mandatory medical examinations for drivers are required, among other things, by the employment relationship, the performance of tasks related to business activity, or the expiration of the validity of the relevant documents. Driver medical examinations aim to assess the physical and mental health of individuals engaged in vehicle operation. This allows for the detection of any health deviations that may affect the ability to drive a vehicle safely.